A COMPARATIVE EFFECT OF COMMUNICATIVE APPROACH WITH AND WITHOUT PICTURE SERIES ON THE EIGHTH GRADE STUDENTS’ WRITING COMPETENCY AT SMP NEGERI 5 AMLAPURA - ., Pande Made Sugiri Adi Nandha; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini adalah penilitian eksperimental yang berfokus pada tiga permasalahan utama yang bertujuan untuk menguji dampak dari communicative approach with picture series pada kempetensi menulis siswa dan pada tipe teks. Subjek dari penelitian ini adalah siswa kelas delapan di SMPN 5 Amlapura. Communicative approach with and without picture series adalah variabel bebas, sedangkan kemampuan menulis siswa merupakan variabel terikat pada penelitian ini. Desain penelitian ini adalah posttest only control group design. Jumlah populasi sebanyak 9 kelas dengan total siswa 263 siswa. Cluster random sampling dilakukan dalam memilih dua kelas sebagai sampel. Satu kelas sebagai kelompok eksperimental dan satu kelas yang lainnya sebagai kelompok kontrol. Posttest dilaksanakn di akhir treatment dan hasil dari posttest dianalisis secara deskriptif dan inferensial. One-way ANOVA digunakan untuk mengetahui perbedaan kompetensi menulis diantara dua kelompok. Hasil dari penelitian ini menunjukkan bahwa terdapat perbedaan yang signifikan diantara dua kelompok dalam kompetensi menulis siswa. Dapat disimpulkan bahwa communicative approach with picture series menunjukkan dampak positif dalam kompetensi menulis siswa.Kata Kunci : Communicative approach, picture series, kompetensi menulis This study was and experimental study which focused on the three major problems that were aimed to test the effect of communicative approach with picture series on the students writing competency and on the text types, descriptive and narrative text. The subject of this study was the eighth grade students of SMPN 5 Amlapura. The independent variable was communicative approach with and without picture series and the dependent variable was writing competency. The research design of this study was posttest only control group design. The number of population was 9 classes with total number of the students were 263 students. Cluster random sampling was done in choosing the two classes as samples. One class was experimental group and the other one was control group. Posttest was administered at the end of the treatment and analyzed descriptively and inferentially. One-way ANOVA was used to know the differences between groups in writing competency. The result showed that there was significant differences between the two teaching techniques on students’ writing competency. In conclusion, communicative approach with picture series showed positive effect on writing competency.keyword : communicative approach, picture series, writing competency